2014
DOI: 10.1111/bjdp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Friendlessness and theory of mind: A prospective longitudinal study

Abstract: Chronic friendlessness in childhood predicts adverse mental health outcomes throughout life, yet its earliest roots are poorly understood. In theory, developing a theory of mind (ToM) should help children gain mutual friends and one preschool study (Peterson & Siegal, 2002. Br J Dev Psychol, 20, 205) suggested a cross-sectional connection. We therefore used a 2-year prospective longitudinal design to explore ToM as a predictor of mutual friendship in 114 children from age 5 to 7 years after controlling potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
97
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 64 publications
2
97
2
2
Order By: Relevance
“…Research on typically developing individuals and non-ASD clinical populations suggests an association between social cognition and functioning. For instance, Fink, Begeer, Peterson, Slaughter, and de Rosnay (2015) found that typically developing children with mutual friends outperformed typically developing children without a mutual friend on a battery of ToM tasks, indicating that poor social cognition may be associated with a lack of quality friendships in childhood. Additionally, a meta-analysis of the impact of social cognition on functioning in schizophrenia found that social cognition was strongly related to functional outcomes, with the strongest associations being between ToM deficits and functional outcomes (Fett, Viechtbauer, Penn, van Os, & Krabbendam, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on typically developing individuals and non-ASD clinical populations suggests an association between social cognition and functioning. For instance, Fink, Begeer, Peterson, Slaughter, and de Rosnay (2015) found that typically developing children with mutual friends outperformed typically developing children without a mutual friend on a battery of ToM tasks, indicating that poor social cognition may be associated with a lack of quality friendships in childhood. Additionally, a meta-analysis of the impact of social cognition on functioning in schizophrenia found that social cognition was strongly related to functional outcomes, with the strongest associations being between ToM deficits and functional outcomes (Fett, Viechtbauer, Penn, van Os, & Krabbendam, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research on children with learning disabilities also has identified a wide array of social skills deficits that impede social problem solving and effective engagement with peers (Wiener, 2004). Similar to children with intellectual disability, these limitations include both social-cognitive errors such as misunderstanding social behaviors and failure to recognize the consequences of their own actions (Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015), and social communication problems such as difficulties generating conversation and communicating clearly enough to be understood (McCabe & Meller, 2004). In addition to functional limitations, children with learning disabilities often display behavioral excesses and poor emotional regulation skills in the form of disruptive and aggressive behaviors that alienate peers (Metsala, Galway, Ishaik, & Barton, 2017).…”
mentioning
confidence: 99%
“…It is widely accepted that this socio-cognitive ability plays a major role in children’s everyday social interactions with others. Indeed, extensive research shows that ToM predicts children’s social competences in such domains as prosocial behavior, interpersonal interaction, and popularity with peers (Astington & Jenkins, 1995; Davis-Unger & Carlson, 2008; Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015; Mizokawa & Koyasu, 2015; Slaughter, Imuta, Peterson, & Henry, 2015; Watson, Nixon, Wilson, & Capage, 1999). Impairments in ToM have also been associated with debilitating socio-cognitive deficits such as autism, severe conduct problems, and psychopathy (Baron-Cohen, Tager-Flusberg, & Cohen, 1994; Blair et al, 1996; Frith & Happé, 1994; Sharp, 2008).…”
mentioning
confidence: 99%